Exploring TikTok's Effectiveness for Local Brand Promotion: A Case Study of Conseva in Indonesia - Tjandrawibawa, Paulina (Universitas Ciputra, 2024)
This study looks into the efficiency of TikTok as a promotional tool for Conseva, an Indonesian company that specialises in fashion accessories and stationery. With an emphasis on reaching a bigger audience, particularly Indonesian women aged 25-34, the study uses a mixed-methods approach to evaluate TikTok's influence on brand awareness, audience engagement, and consumer behaviour. The study examined four different types of films for the Conseva Arctic collection, showing the difficulty of properly engaging the audience and driving customer behaviour through TikTok content. The findings highlight the importance of storytelling and hashtag strategies in digital marketing, emphasising the need for a more nuanced understanding of hashtag success on TikTok. The study's findings add to the expanding conversation about digital marketing by providing insights into the obstacles and opportunities connected with using TikTok as a promotional medium for local brands. However, the study's shortcomings, such as the inability to measure long-term impact and the emphasis on specific material types, should be taken into account when interpreting the results. Future research may address these limitations and expand our understanding of TikTok as a promotional tool for local brands.